Morphological and Cellular Alterations by Gamma Radiation and Grew Under Drought ( 31 ) Journal of Stress in Wheat (Triticum aestivum L.) (Journal of Nuclear Technology in Applied Science, 2018)
Gamma radiation and polyethylene glycol (PEG) are widely used in various fields of research to induce stress and study its effects on plants. In this investigation, morphological characterization, as well as cellular and extracellular structure, were studied in wheat cultivar Sids 13.Gamma radiation at doses of 50 and 100 Gy negatively affected shoot and root lengths, causing reductions of 3 cm and 8 cm (shoot) and 2 cm and 5 cm (root), respectively. Similarly, PEG concentrations of 10%, 15%, and 20% led to decreases in shoot length by 8, 11, and 13 cm and in root length by 5, 7, and 8.5 cm, respectively. The combined effects of gamma radiation and PEG further intensified the reductions in shoot and root lengths, with decreases ranging from 10 to 15 cm and 5 to 8.5 cm, respectively.Gamma radiation and PEG also affected the cellular and ultrastructural integrity of wheat, as revealed by light microscopy, transmission electron microscopy (TEM), and scanning electron microscopy (SEM). These techniques showed changes in cell size, cell wall thickness, organelle morphology, and other intracellular structures. This study highlights the morphological and cellular impacts of radiation doses, PEG concentrations, and their combined effects on wheat cv. Sids 13.
Keywords: Radiation; Wheat; Polyethylene Glycol (PEG